2021
DOI: 10.1002/jor.25039
|View full text |Cite
|
Sign up to set email alerts
|

Landing biomechanics deficits in anterior cruciate ligament reconstruction patients can be assessed in a non‐laboratory setting

Abstract: Landing biomechanics provide important information pertaining to second anterior cruciate ligament (ACL) injury risk in patients following ACL reconstruction (ACLR). While traditional motion analysis technologies are often impractical for use in non-laboratory settings, methods to assess landing biomechanics which are inexpensive, portable, and user-friendly have recently been developed and validated. The purpose of this study was to compare landing kinematics and kinetics between ACLR patients and uninjured c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 52 publications
(108 reference statements)
2
21
0
Order By: Relevance
“…As evidence has shown that deficits in frontal plane hip mechanics and postural stability may contribute to second ACL injury risk [ 34 ], the inclusion of hip joint kinematics may be a better predictor of ACL rupture risk than analysis of knee joint kinematics alone. A recent study by Peebles et al [ 35 ] found reduced symmetry in individuals with ACLR compared to controls, but found no between-group difference in knee FPPA in a bilateral landing. However, their work revealed a significant difference in knee kinematics during unilateral landing [ 35 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As evidence has shown that deficits in frontal plane hip mechanics and postural stability may contribute to second ACL injury risk [ 34 ], the inclusion of hip joint kinematics may be a better predictor of ACL rupture risk than analysis of knee joint kinematics alone. A recent study by Peebles et al [ 35 ] found reduced symmetry in individuals with ACLR compared to controls, but found no between-group difference in knee FPPA in a bilateral landing. However, their work revealed a significant difference in knee kinematics during unilateral landing [ 35 ].…”
Section: Discussionmentioning
confidence: 97%
“…A recent study by Peebles et al [ 35 ] found reduced symmetry in individuals with ACLR compared to controls, but found no between-group difference in knee FPPA in a bilateral landing. However, their work revealed a significant difference in knee kinematics during unilateral landing [ 35 ]. Based on our data and current literature, it is suggested that unilateral landing tasks may be more proficient at detecting asymmetries and that there may be a need to assess both the hip and the knee for asymmetries between limbs of individuals with ACLR.…”
Section: Discussionmentioning
confidence: 97%
“…Data collection was completed for ACLR patients in a local rehabilitation facility, while data collection for landing controls was completed in a university athletic center (Peebles et al, 2021). All participants wore standardized neutral cushioning running shoes (Air Pegasus, Nike Inc., Beaverton, Oregon).…”
Section: Data Collectionmentioning
confidence: 99%
“…All participants wore standardized neutral cushioning running shoes (Air Pegasus, Nike Inc., Beaverton, Oregon). Participants completed seven bilateral drop vertical jumps, with a forward distance of half the participant's body height, and seven unilateral drop landings on each limb, during which participants dropped off of a 31 cm high box, landed on a single limb and held the unilateral landing for two seconds (Peebles et al, 2021).…”
Section: Data Collectionmentioning
confidence: 99%
“…They assessed movements patterns (landing biomechanics) in a nonresearch setting, demonstrating equivalence to laboratory measures. This study is an important step toward providing quantitative injury risk metrics in a clinical setting that can be used for return to sport decision‐making 33 …”
mentioning
confidence: 99%